Surgical outcomes in canine lymphoplasmacytic stomatitis: a retrospective study of 42 dogs (2012–2022) - Ford, Jordan; Bell, Cynthia; Donovan, Taryn A.; Martel, Django (Frontiers in Veterinary Science, 2025)
Lymphoplasmacytic oral mucosal inflammation (stomatitis) in canine patients is common and non-specific. Contact lesions (CL) secondary to periodontal disease are particularly common. Dogs with CL may or may not have canine chronic ulcerative stomatitis (CCUS), yet clinicians are often faced with making treatment decisions without a clear diagnosis. Some may expect canine patients to be treated similarly to feline chronic gingivostomatitis patients, for whom partial- to full-mouth extractions remain the primary intervention. Because this assumption may lead to inappropriate care, clear recommendations for surgical management are needed for canine patients. This retrospective review (2012–2022) evaluated 42 dogs with lymphoplasmacytic stomatitis treated surgically at a dental specialty service. We hypothesized that only a minority of these patients require full-mouth exodontia. Patients were initially stratified as CL or CCUS based on lesion distribution and radiographic findings and reclassified based on treatment response. Clinical outcomes were categorized as complete, partial, or absent response to treatment(s), including COHAT, salvage exodontia, rescue medical management, chronic immunosuppression, and home oral hygiene. Associations between demographic and clinical variables with surgical and clinical endpoints were evaluated using descriptive statistics and chi-square analyses. Small breeds (median 5.4 kg) predominated and were significantly more likely to reach edentulism for any reason. Buccal lesions adjacent to maxillary canine and fourth premolar teeth were most common, but over 60% of cases had mucosal changes beyond the classic paradental lesions. Ultimately, 31% were confirmed as CL and 50% as CCUS. Only 24% underwent salvage exodontia, and 17% were rendered edentulous for mucosal disease management. Achieving edentulism was more common in CL cases (54%) compared to CCUS cases (33%). Most dogs (81%) achieved complete resolution, primarily through treatment of periodontal disease (62%). CL cases showed high response rates to periodontal therapy (83%), while a subset of CCUS patients underwent salvage exodontia (20%) or immunosuppression (5%). The majority of dogs with lymphoplasmacytic stomatitis, including many diagnosed as CCUS, respond to periodontal disease management without full-mouth extractions. These findings support a conservative, staged treatment approach and underscore the need for standardized diagnostic criteria in canine oral inflammatory disease.